Efforts to Improve Learning Outcomes of Volleyball Underwear Passing Through Audio Visual Media For Grade V Students of SDI BTN IKIP 2 Makassar - Akram, Syahril; Hudain, Muh. Adnan; Saharullah, Saharullah; Ridwan, Andi; Wahyuddin, Wahyuddin (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the improvement of learning outcomes of underhand passing in volleyball games through audio-visual media for class V SDI BTN IKIP 2 Makassar. This study uses a qualitative approach and descriptive analysis qualitative. The type of research is Classroom Action Research (CAR) which is carried out in two cycles with each cycle including planning, implementation, observation, and reflection. The subjects of this study were 23 students of class V SDI BTN IKIP 2 Makassar. Data collection techniques used in this study were tests, observations, and documentation. Data analysis techniques in this study used quantitative descriptive analysis. The results of this study indicate a change in that audio-visual learning media can improve the learning outcomes of class V students in the PJOK subject of volleyball underhand passing. In the first cycle, it was shown that out of 23 students, the student's learning efforts had begun to show a significant increase because 16 students had completed it with a percentage of 69.56% and 7 students had not completed it with a percentage of 30.43%, which means that it is still far from the expected success indicator and in Cycle II there has been a very significant increase of 23 students completing it with a percentage of 100%. From these results, the research ended in cycle II because it had reached the success indicator.